1999
DOI: 10.1016/s0735-1097(99)00363-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a novel rectilinear biphasic waveform with a damped sine wave monophasic waveform for transthoracic ventricular defibrillation

Abstract: This study demonstrates a superior efficacy of rectilinear biphasic shocks as compared with monophasic shocks for transthoracic ventricular defibrillation, particularly in patients with a high transthoracic impedance. More important, biphasic shocks defibrillated with nearly 60% less current. The combination of increased efficacy and decreased current requirements suggests that biphasic shocks as compared with monophasic shocks are advantageous for transthoracic ventricular defibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 27 publications
1
33
0
2
Order By: Relevance
“…These studies, performed primarily to support US Food and Drug Administration clearance of new biphasic waveforms, documented that a variety of biphasic shock doses can terminate VF at least as effectively as conventional monophasic shocks of 200 J. [21][22][23][24] More recent studies have described the performance of specific biphasic energy doses during attempted resuscitation from in-hospital and out-of-hospital cardiac arrest. High VF termination rates have generally been reported for initial 150- to 200-J biphasic shocks delivered from first-responder AEDs.…”
Section: Stiell Et Al Randomized Trial Of Biphasic Defibrillation Energymentioning
confidence: 99%
“…These studies, performed primarily to support US Food and Drug Administration clearance of new biphasic waveforms, documented that a variety of biphasic shock doses can terminate VF at least as effectively as conventional monophasic shocks of 200 J. [21][22][23][24] More recent studies have described the performance of specific biphasic energy doses during attempted resuscitation from in-hospital and out-of-hospital cardiac arrest. High VF termination rates have generally been reported for initial 150- to 200-J biphasic shocks delivered from first-responder AEDs.…”
Section: Stiell Et Al Randomized Trial Of Biphasic Defibrillation Energymentioning
confidence: 99%
“…As the field of clinical defibrillation matured, numerous studies were devoted to find the optimal shock waveform that would accomplish defibrillation with minimal delivered energy. It was shown that morphologically distinct waveforms have different defibrillation efficacies in both experimental studies (18,19,26,32,42) and theoretical studies using lumped models (16,43). However, the experimental studies that elucidate mechanisms for differences in defibrillation efficacies of the various waveforms are lacking.…”
mentioning
confidence: 99%
“…29 This delay is difficult to justify in light of the first-shock efficacy of Ͼ90% reported by current biphasic defibrillators. 28,[35][36][37][38][39] AED manufacturers should seek innovative methods to decrease the amount of time chest compressions are interrupted for AED operation. Training materials for lay rescuers should emphasize the importance of continued CPR until basic or advanced life support personnel take over CPR or the victim begins to move.…”
Section: -Shock Protocol Versus 3-shock Sequencementioning
confidence: 99%